The role of international trade liberalization agreements in protecting the environment - غزال عبد اللطيف (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Issues of environmental protection have gained greater attention in recent years, due to increased knowledge of their risks and effects on humans, animals, plants, and climate. Therefore, today they constitute a concern for countries, concerned organizations, and specialists alike, which necessitates concerted efforts in various political, economic, or social fields to address concerns. The environment is taken into consideration, and of course these issues are closely linked to the liberalization of international trade and its relevant agreements. This research will study the provisions for protecting the environment in international trade agreements, which are provisions that are mainly contained in the World Trade Organization agreements in addition to preferential trade agreements, by reviewing those provisions. Discussing them and showing how they were applied and their effectiveness in responding to environmental challenges.